Emergency department nurses' role transition towards emergency nurse practitioner: A realist-informed review. (January 2022) - Putri, Arcellia Farosyah; Tocher, Jennifer; Chandler, Colin
Abstract: Background: The integration of emergency nurse practitioner (ENP) services in emergency departments (EDs) has been well established, especially in high-income countries such as the United Kingdom, the United States and Australia. Different types of reviews, including integrative, literature and systematic, have been carried out to examine evidence regarding the impact of ENPs on the quality of ED services. Unfortunately, there is still limited explanation of the influencing factors that may result in a successful transition process from Registered Nurse to Emergency Nurse Practitioner. This review aims to understand these factors. Methods: A realist approach (RAMESES) guided this review. CINAHL Plus, MEDLINE, PsycINFO, EMBASE and Web of Science databases were searched to capture studies from 1990 to 2020, combined with policy documents from professional bodies and government websites and relevant references from identified sources. Realist data analysis was carried out on the included articles to understand how context, mechanism and outcomes related to the ED nurses' role transition. Results: Forty-eight articles were included. There were differences in preparatory education and scope of practice of the role. The review configured various contexts, mechanisms and outcomes of the role transition along with their interactions. Conclusion: The findings provide a comprehensive understanding regarding the emergency nurses' role transition, with a view to providing better insights and explanations to interested parties who would like to integrate the ENP service in their ED. Highlights: The integration of emergency nurse practitioner (ENP) services into emergency departments (EDs) is progressing at variable speeds in different countries. The realist-infomed review provides an explanation of factors that may affect the success of the transition process of a registered nurse to emergency nurse practitioner in the ED.